Methane Production From Different Parts of Corn Stover via a Simple Co-culture of an Anaerobic Fungus and Methanogen - Li, Yuqi; Hou, Zhesheng; Shi, Qicheng; Cheng, Yanfen; Zhu, Weiyun (Frontiers in Bioengineering and Biotechnology, 2020)
To determine ways to improve the utilization of corn stover, this study investigated methane production from different parts of corn stover using a simple co-culture of an anaerobic fungus (Pecoramyces species) and methanogen (Methanobrevibacter species). The simple co-culture was incubated with the stem pith, leaf blade, or stem bark of corn stover (as substrates) at 39°C for 72 h. The results showed that the stem bark had the lowest (P < 0.05) digestibility (38.0 ± 1.36%) and neutral detergent solubles, that is, cell solubles (31.6 ± 0.45%), and the highest (P < 0.05) lignin content (4.8 ± 0.56%). The leaf blade had a significantly higher methane conversion rate (56.6 ± 0.76 mL/g digested substrate) than the stem pith (49.2 ± 1.60 mL/g digested substrate), even though they showed similar levels of methane production (42.4 ± 1.0 mL and 40.9 ± 1.35 mL, respectively). Both the leaf blade and stem pith of corn stover have the potential to produce methane in a simple co-culture of an anaerobic fungus and methanogen.